On graded WAG2-absorbing submodule - K. Al-Zoubi; Mariam Al-Azaizeh (Математичні Студії)
Let $G$ be a group with identity $e$. Let $R$ be a $G$-graded commutative ring and $M$ a graded $R$-module. In this paper, we introduce the concept of graded $WAG2$-absorbing submodule. A number of results concerning of these classes of graded submodules and their homogeneous components are given.